Metrics for assessing stability of marsh sill living shorelines: Identifying main drivers of marsh boundary degradation - Limin Sun; Cindy M. Palinkas; William Nardin (PLoS ONE, 2025)
Marsh sill living shorelines are increasingly common nature-based features in coastal estuaries used to mitigate shoreline erosion and enhance coastal resilience. Evaluating the stability of these structures is crucial for shoreline design and coastal management strategies. Although several metrics have been developed to assess the stability of natural tidal marshes, their suitability for the created marshes of living shorelines is still unclear. This research compiles and analyzes data from 18 marsh sill living shorelines in Maryland, USA — nine with continuous sills and nine with segmented sills. We characterize their eco-geomorphic features and hydrodynamics with 15 metrics through both field sampling and remote sensing. Among the 15 metrics, six representative ones are selected to identify the major factors influencing potential marsh boundary degradation in marsh sill living shorelines. Our findings indicate that living shorelines with ponding at the marsh edge have a significantly higher Unvegetated/Vegetated Ratio (p < 0.05) and a lower sediment deposition rate (p < 0.1). Gap/Rock ratio and Relative Exposure Index contribute significantly to differences between living shorelines with and without ponding, explaining 5.46% and 4.41% of the variation, respectively (p < 0.05 for both). Functional marsh width, introduced here as a novel metric, shows a varying relationship with sediment deposition rate depending on whether the deposition rate exceeded or fell below the relative sea level rise. A marsh width of approximately 5–10 meters appears to optimize both cost-effectiveness and sediment accumulation. By integrating data across regional ecosystems, this study advances our understanding of potential degradation processes in living shorelines, offering valuable insights for shoreline design and post-construction maintenance.